Exploiting Body and Place in Thomas Hardy’s Tess of the d’Urbervilles - Catherine Lanone (Cahiers Victoriens et Edouardiens)
Drawing upon Annie Escuret’s epistemocritical method of reading, and on her vision of energy and entropy, this paper considers how, in Thomas Hardy’s Tess of the d’Urbervilles, agricultural steam machines begin to colonize the countryside and seem to violate and dislocate the female body. Whereas Talbothays still offers a pastoral community, Flintcomb Ash is a cold place of abjection where both the land and the women are ruthlessly exploited. This creates a kind of proto-ecofeminist logic, as colonial metaphors are applied to the landscape but also to Tess’s enslaved body, while she toils on the machine, relentlessly exposed to the male gaze. Her kinship with animals goes beyond mere metaphor to connect the plight of doomed birds, mice and snakes and of the vulnerable woman. Tess’s plight may be exceptional, but the exception is part of a wider meditation on instability and seasonal flux, as mutations tear the rural social fabric. Far from being merely pastoral and nostalgic, the novel breaks new ground by engaging with gendered and technological strategies that distort the biotope of Wessex.